(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the questions of military discipline, prophylaxis of criminal offences, are considered among servicemen, and also aim task and way of organization, prophylactic measure in eradication of military offences. Key words: In this article the questions of order of subordination and regulation mutual relations are considered among servicemen, where exposed are concepts of responsibility and prophylaxis of criminal offence in a kind violation of regulation rules of